2001
DOI: 10.1046/j.0953-816x.2001.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Human brain carboxypeptidase B, which cleaves β‐amyloid peptides in vitro, is expressed in the endoplasmic reticulum of neurons

Abstract: Intracellular localization of novel human brain carboxypeptidase B (HBCPB) was investigated in human hippocampus, using immunohistochemistry by confocal laser microscopy and biochemical purification of the homogenate by density gradient ultracentrifugation. The former revealed that the majority of HBCPB was expressed in the endoplasmic reticulum, in which the HBCPB-specific C14-module immunoreactivity was colocalized with GRP78 immunoreactivity, a stress 70 heat shock protein specifically expressed in the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In our studies we have identified carboxypeptidase D, which belongs to a family of enzymes that proteolytically process peptides in the secretory pathway (Arolas et al 2007), as a modifier of Ab toxicity. Previous reports have identified carboxypeptidase B as an enzyme that may degrade Ab intracellularly (Matsumoto et al 2001) by processing its carboxy terminus (Hamazaki 1998). The C terminus of Ab plays an important role in the formation of Ab fibrils (CerdaCosta et al 2007), suggesting that the processing by carboxypeptidases may have an important function in the toxicity of Ab.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies we have identified carboxypeptidase D, which belongs to a family of enzymes that proteolytically process peptides in the secretory pathway (Arolas et al 2007), as a modifier of Ab toxicity. Previous reports have identified carboxypeptidase B as an enzyme that may degrade Ab intracellularly (Matsumoto et al 2001) by processing its carboxy terminus (Hamazaki 1998). The C terminus of Ab plays an important role in the formation of Ab fibrils (CerdaCosta et al 2007), suggesting that the processing by carboxypeptidases may have an important function in the toxicity of Ab.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteases have been shown to be capable of cleaving Ab peptide. There are number of candidate proteases, including trypsin and a-chymotrypsin [27], insulin degrading enzyme [28][29][30], endothelin-converting enzyme [31], carboxypeptidase B [32], angiotensin-converting enzyme [33], plasmin [34,35], neprilysin [36] and cathepsin D [20,21]. However, the enzyme definitively responsible for the physiological degradation of Ab peptide is thus far unclear.…”
Section: Discussionmentioning
confidence: 99%
“…3B and 4B. Although Ab 1- 19 and Ab [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were confirmed in the eluent from Ab 1-40 peptide, only Ab 1-19 was identified from Ab 1-42 peptide under our HPLC conditions in order to quantify the amount of residual Ab 1-40 or Ab 1-42 peptide. However, when the each Ab peptide was pretreated with Al, Fe, or Zn (at a level about 0.25 mM), the degradation of Ab 1-40 and Ab 1-42 peptides by cathepsin D was significantly inhibited by pretreatment of Al above 0.25 mM (Figs.…”
Section: Influence Of Al-pretreatment To Substrates Of Cathepsin Dmentioning
confidence: 96%
See 1 more Smart Citation
“…HBCPB is expressed in a group of neuronal perikarya and ependymal cells in normal brains. In brains of sporadic Alzheimer's disease patients, however, expression of HBCPB in neuronal perikarya is decreased, and the immunorea~tivity is detected in about one third of senile plaque and a portion of activated microglia (2,3). The expression of HBCPB is confined in brain, and is basically divided into two groups: (i) endoplasmi~ reticulum of a group of neurons such as On the other hand, it is recently clarified that ependymal cells are stem cells for particular neurons and glias (4).…”
Section: Introductionmentioning
confidence: 97%